2009
DOI: 10.1111/j.1444-0938.2008.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corneal thickness on intraocular pressure measurements with the Pascal dynamic contour, Canon TX‐10 non‐contact and Goldmann applanation tonometers in healthy subjects

Abstract: Purpose:To investigate the effects of central corneal thickness (CCT) on intraocular pressure (IOP) measurements of the Pascal dynamic contour tonometry (DCT), Canon TX-10 non-contact tonometry (NCT) and Goldmann applanation tonometry measurements (GAT) in healthy subjects. Methods: IOP values of 135 eyes with normal corneas of 135 healthy volunteers were determined by DCT, NCT and by GAT. The CCT was measured using an ultrasonic pachymeter after all IOP determinations had been made. Results: When DCT measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
6
12
0
Order By: Relevance
“…A previous study comparing GAT, DCT and noncontact tonometry (NCT) measurements in healthy subjects confirmed significant correlation between CCT and both NCT and GAT. No significant correlation between CCT and DCT measurements was found [13]. Another study found DCT measurements to be affected by corneal curvature [10,11].…”
Section: Introductionmentioning
confidence: 95%
“…A previous study comparing GAT, DCT and noncontact tonometry (NCT) measurements in healthy subjects confirmed significant correlation between CCT and both NCT and GAT. No significant correlation between CCT and DCT measurements was found [13]. Another study found DCT measurements to be affected by corneal curvature [10,11].…”
Section: Introductionmentioning
confidence: 95%
“…Many previous studies have also included eyes on anti-glaucoma medications. 1,3,8,10,13 The effect of treatment on the hydration properties of the cornea was overlooked as this was not the aim of the present study.…”
Section: 3-8mentioning
confidence: 99%
“…1,3,9,13 The shortcomings of present study were dependency bias since both eyes of a subject was included. Also, certain biases like observer bias may creep in, though measures were taken to avoid same by taking average of multiple readings and masking.…”
Section: 3-8mentioning
confidence: 99%
“…2002; Tonnu et al. 2005; Pelit et al. 2009) and subjects with glaucoma and ocular hypertension (Erdurmus et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of both normal (Tonnu et al. 2005; Pelit et al. 2009) and keratoconus (Edmonds 1993; Papastergiou et al.…”
Section: Discussionmentioning
confidence: 99%